Realizing and Allocating Savings From Improving Health Care Quality and Efficiency - Fox, Daniel M (Centers for Disease Control and Prevention, 2010)
International efforts to increase the quality and efficiency of health care services may be creating financial savings that can be used to improve population health. This article examines evidence that such savings (ie, a quality/efficiency or value dividend) are accruing and how they have been allocated and assesses the prospects for reallocating future savings to improve population health. Savings have resulted mainly from reducing the number of inappropriate or harmful interventions, managing care of people with chronic disease more effectively, and implementing health information technology. Savings to date have accrued to the revenues of public and private collective purchasers of care and large provider organizations, but none seem to have been reallocated to address other determinants of health. Furthermore, improved quality sometimes increases spending.